2005
DOI: 10.1128/jvi.79.17.11115-11127.2005
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 2-Bromo-5,6-Dichloro-1-β- d -Ribofuranosyl Benzimidazole Riboside and Inhibitors of DNA, RNA, and Protein Synthesis on Human Cytomegalovirus Genome Maturation

Abstract: Herpesvirus genome maturation is a complex process in which concatemeric DNA molecules are translocated into capsids and cleaved at specific sequences to produce encapsidated-unit genomes. Bacteriophage studies further suggest that important ancillary processes, such as RNA transcription and DNA synthesis, concerned with repeat duplication, recombination, branch resolution, or damage repair may also be involved with the genome maturation process. To gain insight into the biochemical activities needed for herpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…4B, lanes 8 and 9). Consistently with previous reports, cells treated with these drugs contained concatemeric DNA but virtually no 4-kb DNA fragment derived from mature unit-length genomes (36,40,48). These findings therefore demonstrate that although not cross-resistant to other terminase inhibitors, AIC246 activity is comparably related to the processing (cleavage/packaging) of concatemeric DNA, a process catalyzed by the viral terminase.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…4B, lanes 8 and 9). Consistently with previous reports, cells treated with these drugs contained concatemeric DNA but virtually no 4-kb DNA fragment derived from mature unit-length genomes (36,40,48). These findings therefore demonstrate that although not cross-resistant to other terminase inhibitors, AIC246 activity is comparably related to the processing (cleavage/packaging) of concatemeric DNA, a process catalyzed by the viral terminase.…”
Section: Resultssupporting
confidence: 78%
“…This observation is not consistent with the assumption that AIC246 treatment results in concatemers remaining uncut and not being encapsidated. Recent findings of McVoy and Nixon may offer an explanation for this phenomenon (36,39). While analyzing the effect of BDCRB on HCMV genome maturation, the authors confirmed that BDCRB predominantly acts via blocking the processing of viral concatemer DNA to monomeric genome lengths (36,48).…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…6F), suggesting that maturation may be alleviating the negative impact of foscarnet on LC proliferation and/or viability. The specific bases of these toxic effects are difficult to pinpoint, as foscarnet was reported to only minimally affect the activity of host DNA polymerases at concentrations that completely abrogate viral DNA replication (63). Indeed, no cell loss was observed in treated HFF cultures when viral progeny production was completely blunted (Fig.…”
Section: Cd34mentioning
confidence: 98%
“…The pulse times began at 5 s and increased to 60 s with a 3:1 forward-tobackward ratio. DNA species were visualized by ethidium bromide staining and UV light and then transferred to Nytran nylon membranes (Schleicher & Schuell) and hybridized to specifically detect MCMV DNA using 32 P-labeled DNA from plasmid pON4048 as previously described (19).…”
Section: Vol 82 2008 Cis-acting Sequences In Herpesvirus Genome Matmentioning
confidence: 99%